Wednesday

July 23, 2014

July 23, 2014

Posted by **alice** on Sunday, March 11, 2012 at 10:08pm.

- alg2trig -
**Reiny**, Sunday, March 11, 2012 at 10:12pm2(3y-4)^(3/5) = 54

(3y-4)^(3/5) = 27

3y - 4 = 27^(5/3)

3y = 27^(5/3) + 4

y = (27^(5/3) + 4)/3

= (243 + 4)/3 = 247/3 or 82 1/3

- alg2trig -
**Joe**, Sunday, March 11, 2012 at 11:42pm1-(1/a)/1-(1/a^2)

- alg2trig -
**Steve**, Monday, March 12, 2012 at 10:49ammultiply top and bottom by a^2 to get

(a^2-a)/(a^2-1)

= a(a-1)/(a+1)(a-1)

= a/(a+1)

or, since you seem to like reciprocals so much,

1 /(1+1/a)

:-)

**Related Questions**

alg2trig - 16log4^1/64=x

math alg2trig - how would you find the horizontal and vertical asymptote of y=x+...